2010
DOI: 10.1126/science.1181771
|View full text |Cite
|
Sign up to set email alerts
|

A Tricyclic Aromatic Isomer of Hexasilabenzene

Abstract: Aromatic Silicon Benzene has long intrigued chemists on account of the energy stabilization, termed aromaticity, which arises from π-electron delocalization around its ring framework. A persistent question has been how such stabilization would be impacted were the carbons to be replaced by heavier atoms such as silicon. Abersfelder et al. (p. 564 ) have prepared a benzene analog with Si atoms in pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
215
0
19

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(238 citation statements)
references
References 35 publications
4
215
0
19
Order By: Relevance
“…So-called siliconoids [5] are stable unsaturated neutral silicon clusters that show the characteristic structural features of silicon nanoparticles and surfaces in the molecular regime generally realized through the occurrence of one or more unsubstituted Si atoms [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…So-called siliconoids [5] are stable unsaturated neutral silicon clusters that show the characteristic structural features of silicon nanoparticles and surfaces in the molecular regime generally realized through the occurrence of one or more unsubstituted Si atoms [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…16) and isomers of hexasilabenzene 17,18 have been synthesized as isolable molecules by taking advantage of kinetic stabilization and/or stabilization by base coordination. Their structures and properties have contributed to further understanding of the bonding and structures of organic and heavy main group element p-electron compounds.…”
mentioning
confidence: 99%
“…10 The 2,6 diisopropylphenyl group (Dip) and 2,4,6 triisopropylphenyl group (Tip) have been used for the synthesis of hexasilaprismane (Sekiguchi and Sakurai, 1993), 11 tetrasila 1,3 butadiene (Weidenbruch, 1997), 12 and a chair shaped isomer of hexasilabenzene (Scheschkewitz, 2010). 13 Tokitoh and Okazaki demonstrated that the 2,4,6 tris[bis(trimethylsilyl)methyl]phenyl group (Tbt) can be used successfully for the rst isolation of silabenzene.…”
mentioning
confidence: 99%